fatty acids in waters of Shatt Al-Arab River and northwest Arabian Gulf - Al-Saad, H.T.; Hantoush, A.A.; Alhello, M.A.; Zukhair, M.K. (Mesopotamian Journal of Marine Sciences, 2022)
The particulate fraction of the fatty acids was investigated in water samples collected from different stations along the Shatt Al-Arab River and North-West Arabian Gulf during the period June 1993 to July 1994. Samples were analyzed by gas chromatography. Several qualitative and quantitative differences were observed. In general, palmitoleic acid (16:1), palmitic acid (16:0), heptadecanoic acid (17:0), stearic acid (18:0), oleic acid (18:1) and linoleic acid (18:2) were found to be the most abundant fatty acids in the region. Total particulate fatty acids showed large variations, from 1.45 µg/gm at station 7 (Arabian Gulf) during summer 1993 to 18.91 µg/gm at station 2 (Shatt Al-Arab River at Al-Fao town) during winter 1993. The main sources of odd and even number of fatty acids were phytoplankton and microbial activities, while aquatic plants were missing in most sites.